6.5k views
0 votes
I need your help....​

I need your help....​-example-1
User Murki
by
6.0k points

1 Answer

4 votes

Answer:

Theory : A difference of two perfect squares, A2 - B2 can be factored into (A+B) • (A-B)

Proof : (A+B) • (A-B) =

A2 - AB + BA - B2 =

A2 - AB + AB - B2 =

A2 - B2

Note : AB = BA is the commutative property of multiplication.

Note : - AB + AB equals zero and is therefore eliminated from the expression.

Check : 1 is the square of 1

Check : c1 is not a square !!

Ruling : Binomial can not be factored as the difference of two perfect squares]

cos^2x=0

Explanation:

User Sean Reid
by
6.6k points